Influence of silica source in the catalytic activity and heterogenity of mesoporous vanadosilicates - Shylesh, S.; Mirajkar, Subhash P.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2005)
Vanadium-substituted ordered mesoporous silicates (V-OMS) were synthesized hydrothermally using two common silica sources, viz. fumed silica and tetraethyl orthosilicate, and their surface properties and catalytic activities were evaluated in the liquid phase oxidation of 1-napthol using aqueous H2O2 as an oxidant. The catalysts were characterized by XRD, N-2, adsorption-desorption, DRUV-vis and TPR to evaluate the mesostructural ordering and the local environment of vanadium in the MCM-41 matrix. Characterization data of the fresh calcined catalysts reveal a more ordered hexagonal structure for the V-MCM-41 catalyst prepared by using tetraethyl orthosilicate as the silica source while spent catalyst showed that the material is less stable than the V-MCM-41 catalyst prepared by using fumed silica as the silica source. Further, the observed differences in the selectivity behavior of extracted and calcined forms of both vanadium catalysts shows that the treatment conditions had a decisive role in the formation of extra framework metal species and further in the mesoscopic structural ordering. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 1-napthol; MCM-41; Mesoporous; Oxidation; Vanadium